Mechanical performance evaluation of bamboo fibre reinforced polymer composites and its applications: a review - Nurazzi, N. M.; Norrrahim, M. N. F.; Sabaruddin, F. A.; Shazleen, S. S .; Ilyas, R. A.; Lee, S. H.; M. Padzil, F. N.; Aizat, G.; Aisyah, H. A.; Mohidem, N. A. (Institute of Physics Publishing, 2022)
This paper reviews the mechanical performance of bamboo fibre reinforced polymer composites (BFRPs) for structural applications. Bamboo fibres are very promising reinforcements for polymer composites production due to their high aspect ratio, renewability, environmentally friendly, non-toxicity, cheap cost, non-abrasives, full biodegradability, and strong mechanical performances. Besides, bamboo has its own prospects and good potential to be used in biopolymer composites as an alternative for petroleum-based materials to be used in several advanced applications in the building and construction industry. For bamboo fibre to be reinforced with polymer, they must have good interfacial bond between the polymer, as better fibre and matrix interaction results in good interfacial adhesion between fibre/matrix and fewer voids in the composite. Several important factors to improve matrix-fibre bonding and enhance the mechanical properties of BFRP are by fibre treatment, hybridisation, lamination, and using coupling agent. Moreover, mechanical properties of BFRP are greatly influenced by few factors, such as type of fibre and matrix used, fibre-matrix adhesion, fibre dispersion, fibre orientation, composite manufacturing technique used, void content in composites, and porosity of composite. In order to better understand their reinforcing potential, the mechanical properties of this material is critically discussed in this review paper. In addition, the advantages of bamboo fibres as the reinforcing phase in polymer composites is highlighted in this review paper. Besides that, the bamboo-based products such as laminated bamboo lumber, glued-laminated bamboo, hybrid bamboo polymer composites, parallel bamboo strand lumber, parallel strand bamboo, bamboo-oriented strand board, and bamboo-scrimber have lately been developed and used in structural applications.